The 4-hour work week escape 9-5, live anywhere, and join the new rich - Ferriss, Timothy 1977- (Vermilion, 2011)
Tim Ferriss has trouble defining what he does for a living. Depending on when you ask this controversial Princeton University guest lecturer, he might answer: 'I race motorcycles in Europe', 'I ski in the Andes', 'I scuba dive in Panama', 'I dance tango in Buenos Aires'. He has spent more than five years learning the secrets of the 'New Rich', a fast-growing subculture that has abandoned the 'deferred-life plan' and instead mastered the new currencies - time and mobility - to create a new way of living. Why wait a lifetime for your retirement when you can enjoy luxury now?
Keywords: Quality of life; Part-time self-employment; Self-realization; Self-actualization (Psychology); Success in business; Flextime